2017
DOI: 10.5152/eej.2017.16053
|View full text |Cite
|
Sign up to set email alerts
|

Dental Material Choices for Pulp Therapy in Paediatric Dentistry

Abstract: Objective: The purpose of this study was to assess the restorative choices for pulpal therapy by members of the Australian and New Zealand Society of Paediatric Dentistry (ANZSPD). Methods: Members of the ANZSPD were sent an online survey asking about the procedures that they performed and their choice of dental materials. Results: The respondents were 31 general dentists (GD) and 55 specialist paediatric dentists (PD). Materials used for indirect pulp capping included calcium hydroxide [Ca(OH) 2 ] cement (CHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a study that investigating the material choices of clinicians for indirect pulp capping, it was reported that despite its high success rates as a pulp capping agent, MTA is not widely preferred by clinicians in pediatric dentistry. 18 The high cost of the material and inadequate knowledge regarding the procedure to use MTA are considered as possible barriers to its common usage. 19 In the present study, although MTA was not significantly successful as Biodentin, TheraCal LC and resin-modified GIC, pulpal temperature increase did not reach the critical value (5.5 °C) when MTA was used as an indirect pulp capping agent.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that investigating the material choices of clinicians for indirect pulp capping, it was reported that despite its high success rates as a pulp capping agent, MTA is not widely preferred by clinicians in pediatric dentistry. 18 The high cost of the material and inadequate knowledge regarding the procedure to use MTA are considered as possible barriers to its common usage. 19 In the present study, although MTA was not significantly successful as Biodentin, TheraCal LC and resin-modified GIC, pulpal temperature increase did not reach the critical value (5.5 °C) when MTA was used as an indirect pulp capping agent.…”
Section: Discussionmentioning
confidence: 99%
“…Since its invention, MTA has been tested under laboratory conditions, then in animal studies and in clinical trials [ 3 , 4 , 5 ]. The positive results of these investigations have resulted in MTA becoming a commonly used material in pediatric dentistry and in endodontics [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%